Electrochemical performances of monodispersed spherical CuFe2O4 nanoparticles for pseudocapacitive applications. (October 2019) - Saravanakumar, B.; Ramachandran, S.P.; Ravi, G.; Ganesh, V.; Guduru, Ramesh K.; Yuvakkumar, R.
Abstract: The monodispersed CuFe2 O4 nanoparticles were synthesized and optimized by employing solvothermal method and were studied by employing X-ray diffraction (XRD) method. The obtained products have tetragonal crystalline cubic-spinel type structure belonging to I 4 1 / a m d space group. The Raman and infrared studies analyzed the different vibration and starching modes of metal-oxide and the pure phase of the obtained CuFe2 O4 nanoparticles. The morphology nature of monodispersive CuFe2 O4 nanoparticles can be easily identified from field-emission scanning electron microscopy images, and the role of different molarities of KOH at 1, 5, and 10 M (BS1, BS2, BS3) can be clearly observed. The X-ray Photon spectroscopy (XPS) studies the oxidation states of the Cu-2p, Fe-2p and O-1s in CuFe2 O4 nanoparticles, which validates the XRD data and supports the crystalline formation. The specific capacitance of BS1 is 189.2 F/g at current density 0.5 A/g. As the current density increases, the diffusing rate of electrolyte ions into the electrodes will reduce, which is reflected in the specific capacitance of CuFe2 O4 nanoparticles. The cyclic stability of CuFe2 O4 nanoparticles (BS1) exhibits 84% retention after 1000 cycles of galvanostatic charging and discharging studies and the pattern of curve remains the same, which indicates very good coulomb efficiency after long cycles. Highlights: The specific capacitance of CuFe2 O4 is 189.2 F/g at current density 0.5 A/g. CuFe2 O4 exhibits 84% retention after 1000 cycle's. It exhibits very good coulomb efficiency after long cycles.